Assessment and prediction of vehicular emissions in Commonwealth Avenue, Quezon City at various policy and technology scenarios using simple interactive model (SIM-air) - Caramoan, Ria M.; Rollon, Analiza P.; Vergel, Karl B. N. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
The Simple Interactive Models for Better Air Quality (SIM-air) is an integrated approach model that allows the available information to support the integrated urban air quality management. This study utilized the Vehicular Air Pollution Information System module of SIM-air for the assessment of vehicular emissions in Commonwealth Avenue, Quezon City. The main objective of the study is to assess and predict the contribution of different types of vehicles to the vehicular emissions in terms of PM10, SOX and NOX at different policy and technology scenarios. For the base year 2017, the results show vehicular emissions of 735.46 Tons of PM10, 108.90 Tons of SOX and 2,101.11 Tons of NOX. Motorcycle is the major source of particulates contributing about 52% of the PM10 emissions. Meanwhile, Public Utility Jeepneys contribute 27 percent of SOX emissions and Private Cars using gasoline contribute 39% of NOX emissions. Ambient air quality monitoring was also conducted in the study area for the standard parameters of PM10, SO2 and NO2. Results show an average of 88.11 µg/NCM, 47.41 µg/NCM and 22.54 µg/NCM for PM10, NO2 and SO2, respectively, all were within the DENR National Ambient Air Quality Guideline Values. Future emissions of PM10, NOX, and SOX are estimated at different scenarios. Results show that in year 2030, PM10 emissions will be increased by 186.2%. NOX emissions and SOX emissions will also be increased by 38.9% and 5.5%, without implementation of the scenario
Thesis (Master of Science in Environmental Engineering)--University of the Philippines Diliman
Keywords: Automobiles -- Motors -- Exhaust ga; Air -- Pollution -- Measuremen; Air -- Pollution -- Forecastin; Air -- Pollution -- Philippines -- Quezon Cit; Simple Interactive Models for better air quality (SIM-ai.